(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines the nature, structure, classification, and functional significance of native phraseological units in the English language. Phraseological units, often referred to as idioms or fixed expressions, represent a crucial component of linguistic competence and cultural identity. The study explores theoretical approaches proposed by prominent linguists such as Vinogradov, Koonin, Amosova, and Smirnitsky, highlighting their classifications and interpretations. Special attention is given to the semantic, structural, and pragmatic characteristics of native English phraseological units, as well as their cultural specificity. The article also provides illustrative examples to demonstrate how such units function in discourse. The research emphasizes the importance of phraseological units in enriching language, conveying figurative meanings, and reflecting national mentality.